2011
DOI: 10.1088/0256-307x/28/8/084211
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Near-Field Deterioration Induced by Stimulated Rotational Raman Scattering in Long Air Paths

Abstract: We report the experimental investigation of a stimulated rotational Raman scattering effect in long air paths on SG-III TIL, with a 1053 nm, 20-cm-diameter, linearly polarized, 3 ns flat-topped laser pulse. An intense speckle pattern of near field with thickly dotted hot spots is observed at the end of propagation with an intensity-length product above 17 TW/cm. The Stokes developing from the scattering of the laser beam by quantum fluctuations is characterized by a combination of high spatial frequency compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Further studies in LMJ point out that the IL production must be less than 13.2 TW/cm to suppress SRRS. [4] In our previous studies, [14] we observed intense speckle pattern of near-field with thickly dotted hot spots when IL production is above 17 TW/cm, resulting from the combination of the nonlinear Raman amplification and the linear diffraction propagation effect of the Stokes with a noise pattern arising from the spontaneous Raman scattering. With the construction of the new laser facility, energy of 3 ns pulse has already reached 7500 J, and the propagation distance has exceeded 80 m as well, which means an IL production of about 16.4 TW/cm.…”
mentioning
confidence: 72%
“…Further studies in LMJ point out that the IL production must be less than 13.2 TW/cm to suppress SRRS. [4] In our previous studies, [14] we observed intense speckle pattern of near-field with thickly dotted hot spots when IL production is above 17 TW/cm, resulting from the combination of the nonlinear Raman amplification and the linear diffraction propagation effect of the Stokes with a noise pattern arising from the spontaneous Raman scattering. With the construction of the new laser facility, energy of 3 ns pulse has already reached 7500 J, and the propagation distance has exceeded 80 m as well, which means an IL production of about 16.4 TW/cm.…”
mentioning
confidence: 72%
“…In many researches and applications of high-energy and high-power laser, such as inertial confinement fusion (ICF), the high intensity laser pulses will propagate over long paths in air, so the intensity-length product (intensity multiply transmission distance) could be very large, resulting in various serious nonlinear effects, such as stimulated rotational Raman scattering (SRRS) (Henesian et al, 1985;Herring et al, 1986;Leung et al, 1988;Ying et al, 1993;Wang et al, 2011;Omatsu et al, 2012), which limit the laser intensity and fluence that can be transmitted through the air. Therefore, the SRRS process suppression turns to be one of the key problems to be solved in the application and transmission of the high-energy and high-power laser.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Bordenave and Chies (2006) adopted the scheme that a part of transmission media of air is replaced with inert gas to increase the SRRS threshold distance (Kurnit et al, 1987;Wegner et al, 2004), however, the method is costly to build and maintain. Wang et al (2011) proposed to use transmitting Bragg volume gratings to inhibit SRRS by filtering out the Stokes light, but the tiny SRRS frequency shift and high-intensity laser pulse bring a great challenge to grating fabrication. Skeldon and Bahr (1991) installed the smoothing by spectral dispersion (SSD) on the narrow line-width laser (351 nm) to study the SRRS process, the results showed the threshold of SRRS was increased compared to that of the narrow linewidth laser, however, no detailed explanation and subsequent studies were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, the solutions for suppressing the SRRS process have been pursued. [8][9][10] Smoothing by spectral dispersion (SSD) is originally a smoothing technique to obtain highly smooth focused laser beams in the far field [11] and has produced considerable improvement in this aspect. [12][13][14][15] Skeldon and Bahr [10] proposed that SSD could reduce the SRRS gain in the near field via experiment.…”
Section: Introductionmentioning
confidence: 99%